Security risks management in selected academic libraries in Osun State, Nigeria (2013)
The survival of a library depends to a large extent on how secured its collections are. Security of collections constitutes a critical challenge facing academic libraries in Nigeria. It is against this background that this study investigated the security risks management in selected academic libraries in Osun State, Nigeria. The study adopted a descriptive survey design of the ex-post facto type. The population of the study comprised 145 library personnel and 14,317 registered library users in four selected academic libraries in Osun State while the sample size consisted of all thel45 library personnel and 2% of the registered users to make a total of 432 respondents. Questionnaire and interview with the Chief Librarians of the selected academic libraries were the instruments used for data collection. Data were analysed using frequency distribution and percentages run using statistical package for social sciences (SPSS). The study established that the most prevalent security risks in the libraries included stealing/theft of library materials, mutilation of library materials, defacing, misuse/mishandling of library materials, insect attack, fire outbreak and flood. It also established inadequate funding, shortage of staff/personnel, erratic power supply and lack of institutional security policy/disaster plan as some of the challenges confronting security management in the libraries. Based on the findings, recommendations were made towards improving security management in the libraries.